Power in modern societies - Olsen,Marvin E. (Ed.); Marger,Martin N. (Ed.) (San Francisco, 1993)
When an earlier version of this book, titled Power in Societies, was published in 1970, the topic of social power was still marginal to much sociological thinking. During the ensuing twenty-two years, however, power has become one of the most central concepts in the discipline. The exercise and structuring of social power is now a major concern not only within political sociology but also in general social theory and many other areas such as social stratification, race and ethnic relations, the community, economic sociology, social ecology, and even the family, Sociology has at last rediscovered social power.
Keywords: Power (Social science)